2022
DOI: 10.3390/ijerph19073823
|View full text |Cite
|
Sign up to set email alerts
|

FLOWER: An Approach for Enhancing E-Learning Experience Amid COVID-19

Abstract: The worldwide COVID-19 pandemic has forced higher institutions to shift towards electronic (e) learning. Despite a plethora of research on the responses of higher education institutions to COVID-19 and their shift towards e-learning, research often focuses on the opportunities and/or challenges of e-learning amid COVID-19. Notwithstanding this, limited research has addressed how e-learning experiences can be enhanced among medical students, who often need conventional leaning, especially for practical courses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…It was determined that e-learning was successful and investigated major antecedents of e-learning success in the COVID-19 pandemic ( Elshaer and Sobaih, 2022 ; Jaoua et al, 2022 ). The major motivators for the likely continuance of videoconferencing as a supplement to face-to-face tutorials at Spanish institutions ( Infante-Moro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was determined that e-learning was successful and investigated major antecedents of e-learning success in the COVID-19 pandemic ( Elshaer and Sobaih, 2022 ; Jaoua et al, 2022 ). The major motivators for the likely continuance of videoconferencing as a supplement to face-to-face tutorials at Spanish institutions ( Infante-Moro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the current article is focused on digital skills (DS) as part of 21st-century skills. Previous publications defined six sub-skills of the (DS): digital information skills, digital communication skills, digital collaboration skills, critical thinking digital skills, creative digital skills, and problem-solving digital skills, as in the following concepts ( Table 1 ) [ 13 , 14 , 15 , 20 , 21 , 22 , 23 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent research indicates that DS are required to access the internet, as well as to analyze and utilize online content [ 20 , 21 , 22 , 23 ]. Moreover, research has revealed that some students have the digital skills to be digital natives while others are like digital immigrants [ 21 , 24 , 25 , 26 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, scholars responded quickly to the pandemic and its influence on students and their learning experience. A growing academic body of research was conducted to understand the impacts of COVID-19 on education and learning (e.g., [ 2 , 3 , 4 ]); to highlight the challenges and/or opportunities facing e-learning amid the COVID-19 pandemic (e.g., [ 5 , 6 ]); to stress the value of e-learning using either a formal learning system or social network sites (e.g., [ 7 , 8 , 9 , 10 , 11 ]); to maintain academic performance using e-learning (e.g., [ 12 , 13 ]); to enhance student satisfaction and engagement (e.g., [ 14 , 15 ]); to create positive e-learning experiences (e.g., [ 16 , 17 ]; and to understand education post-COVID-19 pandemic (e.g., [ 18 ]).…”
Section: Introductionmentioning
confidence: 99%